Music therapy research during a pandemic: An accidental experiment in caring for music. Issue 2 (1st November 2021) - Schmid, Wolfgang; Simpson, Fraser; DeNora, Tia; Ansdell, Gary
This article describes how a group of music therapists and a music sociologist working on the AHRC-funded research project Care for Music responded to the situation they found themselves during the 2020‐21 COVID pandemic, both in terms of their practice and the ongoing research project they shared. In particular, the article outlines how the challenging situation has produced interesting new practical, methodological and theoretical perspectives ‐ functioning as a helpful 'accidental experiment'. The article presents three vignettes of music therapists coping with the initial pandemic situation and how they adapted music therapy practice, followed by preliminary reflections on emerging themes from the 'accidental experiment' in relation to the central concern of the AHRC Care for Music research project: the co-creation of mutual 'scenes of care' through music within later life and end of life settings.